2010
DOI: 10.2337/dc10-1006
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Synthesis Is Diminished in Patients With Uncontrolled Diabetes and Restored by Dietary Supplementation With Cysteine and Glycine

Abstract: OBJECTIVESustained hyperglycemia is associated with low cellular levels of the antioxidant glutathione (GSH), which leads to tissue damage attributed to oxidative stress. We tested the hypothesis that diminished GSH in adult patients with uncontrolled type 2 diabetes is attributed to decreased synthesis and measured the effect of dietary supplementation with its precursors cysteine and glycine on GSH synthesis rate and oxidative stress.RESEARCH DESIGN AND METHODSWe infused 12 diabetic patients and 12 nondiabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
252
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 336 publications
(282 citation statements)
references
References 22 publications
21
252
1
8
Order By: Relevance
“…Our findings are in accordance with previous studies in DM [17][18][19][20][21] and DR patients. 11 However, we could not find reports on both IMA and GSH simultaneously in DM and DR patients.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Our findings are in accordance with previous studies in DM [17][18][19][20][21] and DR patients. 11 However, we could not find reports on both IMA and GSH simultaneously in DM and DR patients.…”
Section: Discussionsupporting
confidence: 83%
“…12 Moreover, GSH may be utilized as an antioxidant to neutralize excess FR generated in diabetes. Although GSH deficiency has been reported in diabetes, 21 no previous study has reported its relationship to IMA in both DM and DR patients. Could the lower levels of GSH be a result of elevated IMA values, with a greater utilization of GSH as an antioxidant?…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations